Media Pembelajaran Matematika Materi Pokok Bagun Datar Berbasis Augmented Reality - Muhammad Awal Nur; Raden Wirawan; Ainul Inayah (Unversitas Muhammadiyah Mataram, 2023)
Abstract: Flat shape is one of the subjects in mathematics taught by elementary school students. However, studying the material for flat shapes, students memorize the formulas for the circumference and area of flat shapes. Thus, students feel less interested in learning flat construction material. The purpose of this study was to design and create math learning media for grade 5 elementary school with the subject matter of flat structures using Augmented Reality (AR). The research method uses the Multimedia Development Life Cycle (MDLC) with the stages of concept, design, material collecting, assembling, testing and distribution. System modeling uses UML (usecase, activity, Sequence Diagram). The results of the study have been made flat learning media with features of flat learning media applications consisting of scan markers, info, exits, flat shape objects, explanations, content of flat shape material, formula calculations and application user guides. This learning media can help elementary students class V to get to know flat shapes and calculate the area of flat wake objectsAbstrak: Bagun datar merupakan salah satu pokok bahasan pada mata pelajaran matematika yang diajarkan siswa Sekolah Dasar. Namun, mempelajari materi bagun datar, siswa menghafal rumus keliling dan luas bangun datar. Sehingga, siswa merasa kurang tertarik untuk mempelajari materi bagun datar. Tujuan penelitian ini adalah untuk merancang dan membuat media pembelajaran matematika kelas 5 SD materi pokok bagun datar dengan menggunakan Augmented Reality (AR). Metode penelitian menggunakan Multimedia Development Life Cycle (MDLC) dengan tahapan dengan tahapan concept, design, material collecting, assembling, testing dan distribution. Pemodelan sistem menggunakan UML (usecase, activity, Sequence Diagram). Hasil penelitian telah dibuat Media pembelajaran bangun datar dengan Fitur-fitur aplikasi media pembelajaran bangun datar terdiri dari scan marker, info, exit, objek bangun datar, penjelasan, isi materi bagun datar, perhitungan rumus dan panduan pengguna aplikasi Media pembelajaran ini bisa membantu siswa SD kelas V untuk mengenal bangun datar dan menghitung luas objek bangun datar